RESULTS OF IRON SUPPLEMENTATION FOR REGULAR VOLUNTARY NON- REMUNERATED BLOOD DONORS AT NATIONAL INSTITUTE OF HEMATOLOGY AND BLOOD TRANSFUSION - Nguyen, Huu Ha; Tran, Ngoc Que; Bach, Quoc Khanh; Bui, Thi Mai An; Nguyen, Quang Hao (Tạp chí Sinh lý học Việt Nam, 2023)
Objective: To evaluate the results of iron supplementation for RRVBD at the National Institute of Hematology and Blood Transfusion. Subjects and methods: Including 279 RRVBD with serum ferritin below 26 ng/ml taking iron tablets containing 35 mg of elemental iron. Cross-sectional description, prospective study. Results: The proportion of RRVBD taking iron tablets and testing on time is 43.4%, the proportion of RRVBD taking enough iron tablets and not coming to the test on time is 18.6%. Hematological parameters of RRVBD taking iron tablets are within the normal range. The group of RRVBD taking enough iron tablets and testing on time: the mean serum ferritin concentration before taking iron tablets is 15.8 ± 5.5 ng/ml and after taking iron tablets is 24.7 ± 14.9 ng/ml, the proportion of RRVBD with ferritin returning to normal range after taking iron tablets is 39.7%. In the group of RRVBD not taking iron tablets or not taking enough iron tablets, serum ferritin before iron intake is 18.1 ± 5.3 ng/ml and after iron intake is 14.2 ± 10.9 ng/ml, the proportion of blood donors having serum ferritin returning to normal range after iron intake is 7.8%. In the group of RRVBD taking enough iron tablets and not coming to the test on time, the mean serum ferritin concentration before iron intake is 16.5 ± 5.9 ng/ml and after iron intake is 28.8 ± 17.1 ng/ml, the proportion of RRVBD with serum ferritin concentration returning to normal range after blood donation is 51.9%. Conclusion: The RRVBD group, upon consuming sufficient iron and undergoing timely examinations, displayed an increased average serum iron concentration compared to their levels prior to iron supplementation, whereas the subgroup that either lacked adequate iron intake or took insufficient iron exhibited a decreased average serum ferritin concentration compared to their levels prior to initiating iron intake.